An empirical analysis of the relationship between income structure and risk: Evidence from five Asian countries - Sally, Nattha (2017)
Bank is a business that faces many risks, resulting to an increase of an important of risk diversification. The purposes of this dissertation are to find the effect of bank income structure on bank risk and to see whether the income diversification is benefit in Hong Kong, Japan, Singapore, South Korea, and Taiwan over the period of 2007–2016 which was found that the trend of change in noninterest income in Japan, Singapore, South Korean and Taiwan increases over the period study, while there is just a graduate change of income structure in Hong Kong.